Water resources in Germany: Increasingly polluted and regionally overused - Astrid Cullmann; Greta Sundermann; Nicole Wägner; Christian R. von Hirschhausen; Claudia Kemfert (DIW Weekly Report, 2022)
The effects of the climate crisis are worsening water shortages, not only in the Global South but also in Europe, for example in the Berlin-Brandenburg region. Due to inadequate pricing of surface and groundwater abstraction and a lack of regulatory instruments, water overuse is occurring in some regions of Germany. Overuse is especially an issue for industry, which has contractually secured high volumes of water withdrawals at very low cost. In addition, there is extensive water pollution as a result of contaminants released into water bodies by households, industry, sewage treatment plants, and agriculture, which further reduces the clean water supply. In particular, nitrate pollution due to intensive fertilization in agriculture is an increasing problem. As a consequence, households and businesses must bear the additional costs, for example due to increasing costs for drinking water treatment. Organic farming can improve water quality; sanitary innovations such as urine-diverting dry toilets (UDDTs) can also contribute. This Weekly Report summarizes current research results and contributes to the German National Water Strategy, a series of measures to be taken by 2030 to address the inter-generational challenges of water management.
Keywords: Q15; Q53; Q58; 330; water; resources; pollution; nitrate concentration; water prices